COMIENZA EL DIÁLOGO DEL LIBRO DE LA VIDA. - MANTAS ESPAÑA, PEDRO (Revista Española de Filosofía Medieval, 2025)
The article focuses on the prologue of the "Dialogue of the Book of Life," written by Rodrigo, Archbishop of Toledo, where the interpretation of the Scriptures and the relationship between the Old and New Testaments are addressed. It criticizes the idolatry and deviation of the Jewish people from the truth, emphasizing that the revelation of Jesus Christ fulfills the prophecies of the Old Testament. Additionally, the structure of the book is mentioned, which is divided into eight volumes, each dedicated to fundamental themes of the Catholic faith, such as the Trinity, the Incarnation, and the resurrection. The author expresses his desire for the work to serve to illuminate the truth of the Gospel and strengthen the faith of believers.